(untitled) (Altre Modernità, 2021)
This essay examines Scandorama, a graphic novel from 2018 scripted by the Finland-Swedish writer Hannele Mikaela Taivassalo and drawn by the Kenyan- Swedish artist Catherine Anyango Grünewald. The work is read as a comment to unsettling trends in contemporary Scandinavia such as rising nationalisms, antiimmigrant sentiments, and the destruction of nature. Special attention is given to how the issues of building walls and transgressing borders are recorded not only on a verbal level but, first and foremost, to the ways in which these concerns are entrusted to the visual code of comics. It is argued that the chromatic structure employed in the book creates a visual subtext expressing the dystopian theme embedded in Scandorama. Through the use of a single colour, blue, in a monochrome storyworld, the idea of erecting walls and transgressing borders is backed up and expressed in at least three contexts investigated in the article: (1) ‘othering’; (2) architecture; (3) body and mind. Here, the dramaturgical potential of colour combines with motives such as government surveillance, loss of individualism, genetic engineering, futuristic technology, environmental destruction, and urban settings to produce a dystopian ‘blueprint’.